Global, regional, and national burden of multiple myeloma, 1990 to 2021 and predictions to 2035: an analysis of the Global Burden of Disease Study 2021 - Xin Miao; ZhaoXian Wang; HanYu Wang; XiaoYu Zeng; JiaHao Wang; Bing Luo; Ye Yang; JiaFu Yang; Lu Zhao (Frontiers in Medicine)
Background and objectiveMultiple myeloma (MM) is the second most common haematologic malignancy. This study aimed to assess the global burden of multiple myeloma across 204 countries and territories from 1990 to 2021.MethodsThe data for this study were obtained from the Global Burden of Disease (GBD) 2021 dataset, which provides comprehensive information on the global and regional burden of 369 diseases, injuries, and 88 risk factors across 204 countries and territories from 1990 to 2021. We analyzed the incidence, mortality, disability-adjusted life years (DALYs), and disease-related risk factors of MM from 1990 to 2021. Age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized DALYs rate (ASDR) were calculated and analyzed. We also analyzed trends over time by gender and age, and assessed the impact of socio-demographic index (SDI) on disease burden. In addition, the global burden of MM from 2021 to 2035 was predicted by a Bayesian age-period-cohort (BAPC) model.ResultsIn 2021, there were 148,755 cases of MM globally. From 1990 to 2021, the global ASIR, ASMR, and ASDR increased (EAPC = 0.48, 0.09 and 0.06, respectively). In general, the ASIR, ASMR, and ASDR of MM and SDI levels are positive correlated, as regions with higher SDI levels normally have higher ASIR, ASMR, and ASDR. The incidence and mortality rates were higher in males than in females in all age groups, and increased with age before 90 years. We projected that the ASIR, ASMR, and ASDR of MM would obviously increase over the next dozen years through BAPC model.ConclusionThe findings in this study offer valuable insights into the global distribution and magnitude of the MM burden, which may be instructive for better making public health policy and reasonably allocating medical source.